KEWENANGAN PEMERINTAH KABUPATEN/KOTA UNTUK MENYELENGGARAKAN URUSAN PEMERINTAHAN DI BIDANG PENDIDIKAN - KURNIAWAN, VICKI (Jurnal HUKUM BISNIS, 2026)
The authority of district/city governments in education shapes how public education services are planned, funded, and supervised at the level closest to citizens. This study examines the scope of such authority within Indonesia’s allocation of governmental affairs, particularly after Law Number 23 of 2014, while positioning education as a constitutional right and a state obligation that requires a clear division of roles across levels of government. The discussion focuses on key domains of local educational governance, including program planning, capacity building for education personnel, and the management of educational facilities and infrastructure. By analysing the relationship of authority among the central government, provinces, and district/city governments, the study identifies practical points where the boundary of authority may become blurred and where coordination, financing, and quality assurance tend to face challenges. Ultimately, the study proposes normative directions to clarify the allocation of authority and strengthen accountability in local education governance, thereby supporting equitable access and improved quality of education. Keywords: authority, district/city government, education, allocation of governmental affairs